RETRACTED: Impact of Abusive Supervision on Psychological Engagement and Absorptive Capacity Among Students: Mediating Role of Knowledge Hiding - Xiyun Zhang; Jiawen Yu (Frontiers in Psychology)
The research aims to estimate the impact of abusive supervision on psychological engagement and absorptive capacity under the mediating role of knowledge hiding. This study was cross-sectional and data were collected from employees of four different sectors through a questionnaire. The convenient sampling technique was used to collect data from 450 employees. Structural equation modeling (SEM) was used as a data analysis technique because the two-stage SEM technique produces precise and accurate estimates while modeling the path analysis. The output of the measurement model assessment confirmed that all measurement scales were reliable. In addition to this, structural model assessment confirmed that abusive supervision did not significantly predict the absorptive capacity and psychological engagement, although knowledge hiding negatively predicted psychological engagement.